Downstream Effects of Voting on Turnout and Political Preferences: Long-Run Evidence from the UK - Jonas Jessen; Daniel Kühnle; Markus Wagner (Institute of Labor Economics (IZA), 2021)
Does voting have downstream consequences for turnout and political preferences? While research initially showed strong support for the notion that the experience of voting fosters civic habits and political engagement, recent work has cast doubt on how universal these patterns are. We contribute to this debate by studying the short- and long-term impact of earlier voting eligibility on subsequent turnout and political preferences using rich panel data from the UK. Exploiting the eligibility cut-off for national elections within a regression discontinuity design, we document a short-run increase in party identification, political interest and democratic norms for those able to vote earlier. However, these short-term effects quickly fade away and do not translate into permanent changes in turnout propensity or political preferences. Our results imply that the transformative effects of voting are short-lived, at most, in a setting with low institutional barriers to vote.
Keywords: D01; D70; D72; 330; voting; turnout; downstream effects; political preferences; habit; persistence; regression discontinuity